IMPACT OF NUMBER OF IMPLANTS ON OVERDENTURE STRESS - A FINITE ELEMENT ANALYSIS - Butnaru Moldoveanu; Sînziana Anca; Munteanu Florin; Forna Norina Consuela (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study The purpose of our study was to analyze the influence of the number of implants used in IOD on the stress developed in the overdenture, through finite element analysis. Materials and methods A 3D mandible was modeled presenting total edentation and containing two macro-structures of cortical and trabecular bone tissue. An overdenture was also modeled and retained using 2, 4, 6, and 8 implants. Through finite element analysis, simulations were performed using physiological masticatory loading and boundary conditions. Results Stress values were highest when using 2 implants and lowest when using 8 implants, regardless of the analyzed quadrant. Stress concentration areas were located in the same region, at the proximal region of the loading site, where mastication takes place, regardless of how many implants are used. However, differences between analyzed cases were small. Conclusions Increasing the number of implants does reduce the stress values in the overdenture. Because differences reported between simulated cases are small, there is a need for further complex clinical studies to be made, taking into account multiple factors to assess the long term impact of the number of implants on the overdenture.